2009
DOI: 10.1016/j.molcel.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide Analysis of PTB-RNA Interactions Reveals a Strategy Used by the General Splicing Repressor to Modulate Exon Inclusion or Skipping

Abstract: Recent transcriptome analysis indicates that >90% of human genes undergoes alternative splicing, underscoring the contribution of differential RNA processing to diverse proteomes in higher eukaryotic cells. The polypyrimidine tract binding protein PTB is a well-characterized splicing repressor, but PTB knockdown causes both exon inclusion and skipping. Genome-wide mapping of PTB-RNA interactions and construction of a functional RNA map now revealed that dominant PTB binding near a competing constitutive splice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
508
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 422 publications
(567 citation statements)
references
References 34 publications
(82 reference statements)
48
508
3
1
Order By: Relevance
“…For example, exons known to be downregulated by Nova had higher Nova scores in their upstream introns, and exons known to be upregulated by Nova had higher Nova scores in their downstream intron 48 . Similarly, TIA has been shown to upregulate exons when bound to the downstream intron 49 , and PTBP1 has been shown to suppress exon inclusion when bound to upstream introns of weaker splice sites 50 .…”
Section: Deepbind Models Identify Deleterious Genomic Variantsmentioning
confidence: 99%
“…For example, exons known to be downregulated by Nova had higher Nova scores in their upstream introns, and exons known to be upregulated by Nova had higher Nova scores in their downstream intron 48 . Similarly, TIA has been shown to upregulate exons when bound to the downstream intron 49 , and PTBP1 has been shown to suppress exon inclusion when bound to upstream introns of weaker splice sites 50 .…”
Section: Deepbind Models Identify Deleterious Genomic Variantsmentioning
confidence: 99%
“…The splicing-repressive functions of PTB are best studied, although it is also clear that it can promote inclusion of some exons (Xue et al 2009). Like hnRNP A/B proteins, PTB is expressed throughout development, then downregulated in many adult tissues, most notably brain and muscle (Boutz et al 2007a;Makeyev et al 2007).…”
Section: Hnrnp and Sr Proteins In Proliferation And Cancermentioning
confidence: 99%
“…However, more recent work suggested that the splicing regulatory activity can vary for different binding sites as well as for sets of combinatorially acting factors. One example for positiondependent splicing is constituted by the hnRNP protein PTB (Xue et al, 2009;Llorian et al, 2010), an in animals, wellcharacterized regulator of AS that binds to pyrimidine-rich motifs within pre-mRNAs (Sawicka et al, 2008;Wachter et al, 2012). Evidence has been provided that PTB exploits various mechanisms for AS control, including competing with U2 auxiliary factor 65 in binding to the pre-mRNA (Saulière et al, 2006), looping of RNA regions (Spellman and Smith, 2006), and interference with splicing factor interactions required for exon or intron definition (Izquierdo et al, 2005;Sharma et al, 2005).…”
Section: Introductionmentioning
confidence: 99%